Analisis Pola Konsumsi Susu Kental Manis oleh Rumah Tangga Peserta Program Keluarga Harapan di Kota Pekanbaru - Rosalin, Mutia Agnes Almira; Bakce, Djaimi; Yusri, Jumatri (Universitas Islam Kadiri, 2026)
Sweetened condensed milk is one of the most widely consumed dairy product in Indonesia, particularly among low income households due to its affordable price and long shelf life. However, considering its high sugar content and low protein levels make its consumption an important concern in terms of nutritional quality. This study aims to analyze the consumption pattern of sweetened condensed milk among households participating in Program Keluarga Harapan (PKH) in Pekanbaru City based on their socioeconomic characteristics. Primary data were collected through interviews with PKH households in several districts of Pekanbaru City. Data were analyzed using descriptive quantitative methods through cross tabulation to examine variations in sweetened condensed milk consumption according to household size, education level, and occupation of the household head. The results show that most Program Keluarga Harapan households in Pekanbaru regularly consumed sweetened condensed milk. The amount of consumption tends to be lower in households with more family members, while households with lower education levels and head working in the informal sector tend to consumed more sweetened condensed milk. In conclusion, sweetened condensed milk remains the most widely consumed dairy product among Program Keluarga Harapan households, highlighting the need for nutrition education to promote awareness of healthier and more nutritious milk consumption choices.